Edukasi, kartu kontrol dan dukungan kelompok sebaya sebagai upaya pencegahan anemia di Kampung Maryendi Kabupaten Biak Numfor Provinsi Papua: Education, control cards and peer groups as efforts to prevent adolescent anemia in Maryendi Village, Biak Numfor Regency, Papua Province - Manik, Inggrit Rita Uli; Tonapa, Selpiana; Burdam, Agustina (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT Anemia is still a public health problem in Indonesia; as shown by the 2018 Riskesdas results, as many as 3-4 out of 10 adolescent are anemic. Causes of anemia in adolescent include food intake, comorbidities, and lack of consumption of blood supplement tablets (TTD). Compliance with adolescent girls consuming TTD according to standards is also very low at 1.4%. Data from the KIA Ridge Community Health Center from January-May 2023 showed that there were four pregnant women in Maryendi Village and two pregnant women aged < 20 years suffering from anemia. As a preventive measure for anemia in adolescent in Maryendi village, Samofa District, Biak Numfor District, Papua, community service was carried out by providing education, TTD, forming youth groups for peer support, and using TTD control cards. The community service activities were attended by 16 adolescent aged 12–18 years. Most of the adolescent who took part in the activity were 12 years old (37.5%), and most had junior high school education (50%). Tests were carried out before education and after education, with the T test showing a significant increase (p = 0.000). Blood supplementation tablets were given for three months using a TTD control card, and three groups of adolescent were formed as peer support. The three months of mentoring went well with the participation of the adolescent and support from the church and the village government. Keywords: Adolescent health; Anemia prevention; Blood supplement tablets (TTD); Community education; Peer support ABSTRAK Anemia masih menjadi masalah kesehatan masyarakat di Indonesia; ditunjukkan dengan hasil Riskesdas tahun 2018, sebanyak 3-4 dari 10 remaja anemia. Penyebab anemia pada remaja putri diantaranya asupan makan, penyakit penyerta dan kurangnya konsumsi Tablet Tambah Darah (TTD). Kepatuhan remaja putri mengkonsumsi TTD sesuai standar juga sangat rendah 1,4%. Data dari KIA Puskesmas Ridge dari bulan Januari-Mei 2023 terdapat empat ibu hamil di Kampung maryendi dan dua ibu hamil berusia < 20 tahun menderita Anemia. Sebagai tindakan pencegahan terjadinya anemia pada remaja di kampung Maryendi Distrik Samofa Kabupaten Biak Numfor Papua, maka dilakukan pengabdian masyarakat dengan memberikan edukasi, TTD, membentuk kelompok remaja untuk dukungan sebaya dan penggunaan kartu Kontrol TTD. Kegiatan pengabdian masyarakat di ikuti remaja usia 12-18 tahun sebanyak 16 remaja putri. Remaja yang mengikuti kegiatan paling banyak berusia 12 tahun (37,5%) dan Pendidikan terbanyak yang dibangku SMP (50%). Dilakukan tes sebelum edukasi dan setelah edukasi, dengan uji T test menunjukkan adanya peningkatan yang signifikan (p=0,000). Pemberian tablet tambah darah diberikan selama tiga bulan dengan menggunakan kartu kontrol TTD dan terbentuk tiga kelompok remaja putri sebagai dukungan teman sebaya. Pendampingan selama tiga bulan berjalan dengan baik atas partisipasi dari remaja putri, dukungan dari gereja dan pemerintah kampung. Kata kunci: Dukungan; Edukasi masyarakat; Kesehatan remaja; Pencegahan anemia; Tablet tambah darah (TTD)